Pemanfaatan Dana KIPK untuk Mendukung Pendidikan Mahasiswa dari Keluarga Pra-Sejahtera - Dinda R Sibagariang; Raudhatul Jannah; Akbar P Nugraha; Berlianti Berlianti (LP3M INSTITUT KH YAZID KARIMULLAH, 2025)
This study aims to analyze the utilization of the Indonesia Smart Card for Higher Education (KIPK) funds in supporting the education of underprivileged students at the Faculty of Social and Political Sciences, Universitas Sumatera Utara. The findings show that KIPK provides significant benefits both academically, by covering tuition fees and learning needs, and economically, by alleviating the financial burden on families. Additionally, the program supports students in improving their academic achievements. However, challenges such as complex administrative procedures, delays in fund disbursement, and inaccuracies in target beneficiaries remain issues. This study recommends simplifying procedures, enhancing socialization, and evaluating recipient selection to improve the program's effectiveness.